Sex body: A nest of protein mixture - Li, Miao (Frontiers in Cell and Developmental Biology, 2023)
During pachytene stage in mammalian meiosis, the X and Y chromosomes remain largely unsynapsed outside the pseudoautosomal region (PAR), while autosomes are fully synapsed. Then the sex chromosomes are compartmentalized into a “sex body” in the nucleus and are subject to meiotic sex chromosome inactivation (MSCI). For decades, the form and function of the sex body and MSCI have been the subject worth exploring. Notably, a series of proteins were gradually reported to be located on sex body area and were inferred to play an essential role in MSCI, but what proteins actually locate in this area and how these proteins promote sex body formation and MSCI establishment remained unclear. Collectively, DNA damage response (DDR) factors, the downstream Fanconi anemia (FA) proteins and other canonical repressive histone modifications were reported to be associated with sex body. Here, this paper reviews the factors located at sex body area and try to provide new insights to study this mysterious domain.